PENGARUH LAMA TERESAN DAN DIAMETER TEGAKAN JATI TERHADAP PERSENTASE KERUSAKAN KAYU - Soenamo Soenamo; Marnan Mansyur Idris (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Girdling treatment of teak stand before felling not only intended to reduce the teak wood damage but also aimed at reducing log transport costs. On the other hand, prolonged girdling treatment could generate significant disadvantage effect, among others: decreasing total wood volume, degrade forest land fertility, and often inducing wild under growth, etc.This study deals with a research on the extent of the effect of girdling and size of diameter on the logging damages. The study was carried out at Pasar Sore Sub Forest District, at Cepu, Central Java. This study reveals that the extent of the damages are inversely proportional to the girdling time and diameter of the trees. The average damage percentages per trees on one year girlding duration with diameter classes 50 -59 cm, 60 - 69 cm, 70 -79 cm are 3.02 %, 4.17% and 7.41%, while on the two years girdling duration the damage for the same diameter classes are 5.62 %, 6.76 % and 7.08%, respectively.